A Review on Disease Prediction using Image Processing - Pallavi Patil; Kirankumari Patil (Tinta Emas Publisher, 2023)
With the fast growth of modern information technology, in both manufacturing and daily life, digital image processing has developed quickly. In the fields for recognition, medicine, and remote sensing, it makes an immeasurable impact. In this article, the fundamental idea of digital image processing has been explained, accompanied by one of the most recent scientific developments in four distinct domains and an overview and evaluation of the most widely used digital image processing technology. Finally, the document proposes a direction for the field's future development. In the future, it will focus more on AI algorithms and improve the logical structure to handle information more effectively. The fields of miniaturization, intelligence, and convenience are going to develop and expand the application arena of digital image processing through the use of simplified image algorithm.